IMPLEMENTASI KEBIJAKAN TERHADAP PERSEPSI KONSUMEN NUART SCULPTURE PARK SEBAGAI DESTINASI WISATA MINAT KHUSUS - Yuliana Pinaringsih Kristiutami; Erlangga Brahmanto; Swastono Putro Pirastyo (Kepariwisataan: Jurnal Ilmiah, 2019)
Nowadays, tourism growth starts to deal with new segmentation of market, which is special interest tourism. Special interest destinations also come with special interest market segment. To face this situation, management has to heedful and wise to develop some policy to cover tourist perception. Because, perception can affect buying decisions (in this case, affect the tourist to visit the destination). Buying decisions, of course, take an effect on the level of visit and the level of satisfaction of the tourist who visits the destination. As a special interest destination, balancing the tourist need and the management goals are also tricky. For this reason, it is necessary to conduct a study about the Policy Implementation To Tourist Perception In NuArt Sculpture Park As Special Interest Destination. This study is qualitative descriptive study. The focus of this study is to observe three elements which are the place, the actors and the activity. This study aims to observe the tourist activity while visiting NuArt Sculpture Park, and also to find out about the motivation to visit this destination. The sampling technique chooses for this study is purposive sampling technique. Data collecting instrument was planned to use observation, interview, documentation and also triangulation technique. The goal of this study is to deliver a policy model to the special interest destination, especially in the promotions aspect.Keywords: Special Interest Tourism; Perception; Implementation; Policy